Signaling networks in cancer stromal senescent cells establish malignant microenvironment - Yue Zhang; Teh-Wei Wang; Maho Tamatani; Xinyi Zeng; Lindo Nakamura; Satotaka Omori; Kiyoshi Yamaguchi; Seira Hatakeyama; Eigo Shimizu; Satoshi Yamazaki; Yoichi Furukawa; Seiya Imoto; et al. (Proceedings of the National Academy of Sciences, 2025)
The tumor microenvironment (TME) encompasses various cell types, blood and lymphatic vessels, and noncellular constituents like extracellular matrix (ECM) and cytokines. These intricate interactions between cellular and noncellular components contribute to the development of a malignant TME, such as immunosuppressive, desmoplastic, angiogenic conditions, and the formation of a niche for cancer stem cells, but there is limited understanding of the specific subtypes of stromal cells involved in this process. Here, we utilized p16-Cre ERT2 -tdTomato mouse models to investigate the signaling networks established by senescent cancer stromal cells, contributing to the development of a malignant TME. In pancreatic ductal adenocarcinoma (PDAC) allograft models, these senescent cells were found to promote cancer fibrosis, enhance angiogenesis, and suppress cancer immune surveillance. Notably, the selective elimination of senescent cancer stromal cells improves the malignant TME, subsequently reducing tumor progression in PDAC. This highlights the antitumor efficacy of senolytic treatment alone and its synergistic effect when combined with conventional chemotherapy. Taken together, our findings suggest that the signaling crosstalk among senescent cancer stromal cells plays a key role in the progression of PDAC and may be a promising therapeutic target.